La fiscalidad en la historia de Centroamérica y Chiapas: trayectorias historiográficas y posibles caminos, 1760-1840 - Pollack, Aaron; Sarazúa Pérez, Juan Carlos (CIICLA, Universidad de Costa Rica, 2021)
This article focuses on historiography concerned with changes and continuities in the tax systems in Central America and Chiapas between 1760 and 1840. Relatively little research has been undertaken on the latter years of the colonial period, and more attention has been focused, especially in recent years, on the first decades after Independence. The historiography underlines the importance of tax systems for the configuration of the state and the rest of society. The studies considered refer principally to state liquor and tobacco monopolies, tribute and direct contributions, alcabala, the expropriation of ecclesiastical property, and debt. Variations in the relative importance of these income sources in the different territories is examined. The authors propose avenues for future research in the field.